HIV Serodiscordance among Couples in Cameroon: Effects on Sexual and Reproductive Health - Constantin Tchakounté, MSc; Céline N. Nkenfou, PhD; Thibau F. Tchouangueu, MSc; Nicole M. Ngoufack,, MSc; Salomon B. Tchuandom, MSc; Olivier D. Ngono, MSc; Jules-Rogers Kuiate, PhD; Alexis Ndjolo, MD (Global Health and Education Projects, Inc., 2020)
Background and Objectives: One of the main reasons for risky sexual behavior observed in HIV serodiscordant couples despite the knowledge of the partner's status and counselling is childbearing. In Cameroon, there are few reports on HIV serodiscordant couples. This paper describes the influence of HIV on sexual relationships and decision to procreate. Methods: This cross-sectional study was conducted in five health centers. Self-administered questionnaire was used to collect social and demographic information, while semi-structured in-depth individual and couple interviews were used to explore sexual relationships and decisions about fatherhood/motherhood. Blood samples were collected from the couples and tested for HIV to confirm serodiscordance. The data were analyzed using the GraphPad Prism Version 6 software. Results: A total of 53/192 (27.6%) HIV serodiscordant couples participated in the study, and 18/74 (24.32%) HIV positive seroconcordant couples and 32/80 HIV negative seroconcordant couples were used as controls. The majority of HIV-positive partners in serodiscordant couples were women (30/53), of whom 25/30 were on antiretroviral therapy. Nearly half of the respondents (23 /53) reported tensions related to serodiscordance, shown by reduced sex frequency. The use of condoms was not systematically observed among seroconcordant and serodiscordant couples with respective proportions of 55.55% and 20.75% (p = 0.0086). Thirty seven out of 53 HIV serodiscordant couples wanted children, among them, seven couples did not have any and expressed their aspiration for parenthood despite fear of infecting one's partner. Conclusion and Global Health Implications: Sexuality of serodiscordant couples as well as of HIV positive seroconcordant couples was affected by the presence of HIV/AIDS. The desire to procreate may lead couples to adopt risky sexual behaviors. It is important to define specific guidelines for serodiscordant couples in order to improve their sexual life and consequently enable them to procreate with minimal risk of infecting their partner and or to transmit the virus to their baby. Key words: • HIV • Serodiscordance • Sexual health • Childbearing • Cameroon • Reproductive health   Copyright © 2020 Tchakounté et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License (CC BY 4.0) which permits unrestricted use, distribution, and reproduction in any medium, provided the original work, first published in this journal, is properly cited.